CONTRIBUTION TO THE STUDY OF THE EFFECT OF ORGANIC EXTRACTS OF BUNIUM INCRASSATUM ON THE HEMATOLOGICAL, OVARIAN AND UTERINE PARAMETERS OF MATURE FEMALE RABBIT - Chentouh, S.; Boulahbel, S.; Ouldjaoui, A.; Hammoudi, N.; Djebaili, H.; Adjel, F. (University of Eloued جامعة الوادي, 2017)
The objective of this study is to evaluate the impact of the organic extracts of Bunium incrassatum roots, belonging to the Apiaceae family, on some hematological parameter and histomorphological changes of the genital tract. This plant, called ‘Talghouda‘, is widely distributed in the east parts of Algeria. Phytochemical analyzes of the roots of this plant reveal the presence of two coumarins, scopoletin, scoparone Beta-sitosterol, sucrose and oleic acid. The study was achieved on mature rabbits of the local breed (Oryctolagus cuniculus) for 15 days. The animals were divided into five groups, which have daily administered 0, 25, 50, 100 and 200 mg/kg/day respectively doses of organic extract of Bunium incrassatum. The group with dose 0 was taken as a control. After treatment, the rabbits were sacrificed, the blood was collected in heparin tubes and their ovaries and uterus were removed and fixed in 10% formalin and then stained with hematoxylin-eosin. We found that treatment with the organic Bunium Incrassatum extract induces a significant decrease in the level of Triglyceride, Cholesterol in treated rabbits. The results of the histological study revealed a significant increase in the number of primary and secondary follicles in rabbits treated with 50 and 100 mg/kg/day doses and a decrease accompanied by an increase in atretic follicles in rabbits treated with a dose of 200 mg/kg/day, compared to the control group. The study shows that the organic extract of Bunium Incrassatum had estrogenic effects at doses of 50 and 100 mg/kg/day.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Bunium incrassatum, Rabbits, Ovaries, Follicles, Liver, Uterus